Use of maintenance endocrine therapy after chemotherapy in metastatic breast cancer. (December 2016) - Sutherland, S.; Miles, D.; Makris, A.
Abstract: Background: For women with oestrogen receptor+ metastatic breast cancer (MBC), the options for systemic treatment include endocrine therapy (ET) and chemotherapy. For women whose disease is also HER2+, anti-HER2 therapies are also routinely used either with chemotherapy or less commonly with ET. Where chemotherapy is used as initial therapy, treatment is often discontinued due to cumulative toxicity in the absence of disease progression. In this setting, there is the option of introducing ET with the aim of prolonging response and delaying relapse. Methods: Literature review revealed four trials addressing the question of whether there is a benefit from introducing ET following chemotherapy for MBC. We also sought evidence for alternative approaches, including concurrent chemotherapy and ET and continuing chemotherapy until disease progression. Results: The evidence for the use of ET after chemotherapy in MBC is limited, and the trials done were small. Furthermore, they were performed at a time when both the chemotherapy regimens and ET were different from those used currently. Despite these limitations, there is probably a modest improvement in time to progression for the sequential use of ET after chemotherapy but with no overall survival benefit. An alternative approach, particularly considering agents with relatively low toxicity, such as orally bioavailable fluoropyrimidines, is to continue chemotherapy until disease progression. Conclusion: Where chemotherapy for MBC is discontinued due to toxicity, in the absence of progression, the use of ET, with its relatively low toxicity, is a reasonable approach with the aim of delaying relapse.